MICROPROPAGATION OF ECLIPTA ALBA (L.) HASSK. AN IMPORTANT MEDICINAL PLANT OF TRADITIONAL MEDICINE: Life Science-Botany - SHARMA, ARCHANA; SHIKHA BHANSALI; ASHWANI KUMAR (International Journal of Life Science and Pharma Research, 2013)
Eclipta alba was successfully micropropagated using nodal segments as explants. Multiple shoots were obtained by culturing the explants on MS medium supplemented with various concentrations of cytokinins viz., BAP and Kn alone or in combination with auxins (IAA/NAA). Rooting was induced by transferring the obtained multiple shoots to the medium supplemented with various auxins (IAA/NAA/IBA) at different concentrations. The effect of strength of MS medium on root induction was also observed. The in vitro developed rooted plantlets were acclimatized successfully and transferred to soil.